Physiological Functions and Regulation of the Na+/H+ Exchanger [NHE1] in Renal Tubule Epithelial Cells - Garramuño, Patricia (2015)
The sodium-hydrogen exchanger isoform-1 [NHE1] is a ubiquitously expressed plasma membrane protein that plays a central role in intracellular pH and cell volume homeostasis by catalyzing an electroneutral exchange of extracellular sodium and intracellular hydrogen. Outside of this important physiological function, the NHE1 cytosolic tail domain acts as a molecular scaffold regulating cell survival and actin cytoskeleton organization through NHE1-dependent signaling proteins. NHE1 plays main roles in response to physiological stress conditions which in addition to cell shrinkage and acidification, include hypoxia and mechanical stimuli, such as cell stretch. NHE1-mediated modulation of programmed cell death results from the exchanger-mediated changes in pHi, cell volume, and/or [Na+]I; and, it has recently become known that regulation of cellular signaling pathways are involved as well. This review focuses on NHE1 functions and regulations. We describe evidence showing how these structural actions integrate with ion translocation in regulating renal tubule epithelial cell survival.